Renal cancer : contemporary management - Libertino, John A. (Springer New York, 2013)
Renal Cancer: Contemporary Management provides a state of the art overview of the major topics in the field of kidney cancer. The material has been collected from the most current evidence based resources to allow for the appropriate care of these patients. The sections of the book have been structured to give an overview of the major issues dealing with renal cell carcinoma and transitional cell carcinoma of the kidney. The text also reviews the new staging system, discusses familial syndromes of renal cell carcinoma, and provides new perspectives with regard to imaging and managing renal tumors. A valuable resource for physicians and researchers dealing with renal cancer, Renal Cancer: Contemporary Management provides a comprehensive summary of the field that will guide patient management and stimulate further clinical and basic science research efforts.